Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/jfs.12750
|View full text |Cite
|
Sign up to set email alerts
|

The probiotic, Leuconostoc mesenteroides, inhibits Listeria monocytogenes biofilm formation

Abstract: Listeria monocytogenes biofilm formation renders these cells highly resistant to current sanitation methods, and probiotics may be a promising approach to the efficient inhibition of Listeria biofilms. In the present study, three Leuconostoc mesenteroides strains of lactic acid bacteria isolated from kimchi were shown to be effective probiotics for inhibiting Listeria biofilm formation. Biofilms of two L. monocytogenes serotypes, 1/2a (ATCC15313) and 4b (ATCC19115), in dual‐species culture with each probiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 43 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…It is reported that L. sakei from Kimchi are promising anti-noroviral candidates [37]. Studies have shown that L. sakei CRL1862 and L. mesenteroides Com75 could be environmentally friendly agents against foodborne pathogens [38,39]. No study or evidence has however demonstrated that the intake of probiotics may have potential cariogenic or cariostatic effects.…”
Section: Isolation and Identification Of Potentially Cariogenic Microorganismsmentioning
confidence: 99%
“…It is reported that L. sakei from Kimchi are promising anti-noroviral candidates [37]. Studies have shown that L. sakei CRL1862 and L. mesenteroides Com75 could be environmentally friendly agents against foodborne pathogens [38,39]. No study or evidence has however demonstrated that the intake of probiotics may have potential cariogenic or cariostatic effects.…”
Section: Isolation and Identification Of Potentially Cariogenic Microorganismsmentioning
confidence: 99%
“…Interestingly, previous work has found the supernatant from an isolate of L. lactis to have antimicrobial effects on several pathogenic species including Staphylococcus aureus, Escherichia coli O157, and Proteusbacillus vulgaris (Zhang et al, 2013). Similarly, other members of the genera Leuconostoc and Weissella have been shown to have antimicrobial properties, most notably by reducing the formation of biofilms (Quattrini et al, 2020;Shao et al, 2020;Jang et al, 2021). It is therefore plausible that the high copper treatment exhibited lower virulence because it caused species sorting towards non-pathogenic species, and that this affect was possibly compounded by the resulting species potentially having antimicrobial traits.…”
Section: Discussionmentioning
confidence: 99%
“…Several Ln. mesenteroides strains are reported to have anti-listerial, antiviral, or immunomodulatory activities (Seo et al, 2012;Shao et al, 2020). Since the production of exopolysaccharides and bacteriocins are important properties of Ln.…”
Section: Discussionmentioning
confidence: 99%